Comparative Analysis Methods Fullslab Precast Erection of Cost and Time - Susanti, Irriene Indah; Hadi, Dega` Setyawan (NAROTAMA UNIVERSITY, Indonesia, 2020)
The Indonesian government stepped up infrastructure projects in the country for logistical and economic equality equalization, infrastructure in the form of a Freeway. This study aimed to analyze and compare the costs, timing, and precise method in Fullslab Precast erection work on 1 module. The data used are primary and secondary. Using the method of removal/erection with heavy equipment cranes. For the calculation of comparative analysis is obtained by analysis of the cost and time analysis. Field observations, and direct cost analysis calculation, and not directly into the calculations that will be loaded to get the proper method to the cost and time of work. The results of the right method are method 1 Crawler Crane at Rp 206.598.086,00.